2003
DOI: 10.1002/jbm.a.20010
|View full text |Cite
|
Sign up to set email alerts
|

Growth behavior, matrix production, and gene expression of human osteoblasts in defined cylindrical titanium channels

Abstract: The purpose of the current study was to investigate the effect of different diameters of cylindrical titanium channels on human osteoblasts. Titanium samples having continuous drill channels with diameters of 300, 400, 500, 600, and 1000 microm were put into osteoblast cell cultures that were isolated from 12 adult human trauma patients. Cell migration into the drill channels was investigated by transmitted-light microscopy. The DNA content in the drill channels was measured photometrically, collagen type I pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 38 publications
(35 reference statements)
1
67
1
Order By: Relevance
“…[26][27][28]37] with that of Ti-Nb-Zr foam: the apparent Young's modulus matches perfectly that of the bone, but the CS ⁎ is always higher, being about 70 MPa for the high-porosity samples of our study. One of the important characteristics of materials for orthopedic applications is the maximum elastic strain: for bone it is about 1.1%, for the high-porosity Ti-Nb-Z rs p e c i m e n si ti sa r o u n d3 % ,w h i c h guarantees that the implant will not be damaged before the bone [26][27][28]37]. …”
Section: Mechanical Behaviormentioning
confidence: 53%
See 1 more Smart Citation
“…[26][27][28]37] with that of Ti-Nb-Zr foam: the apparent Young's modulus matches perfectly that of the bone, but the CS ⁎ is always higher, being about 70 MPa for the high-porosity samples of our study. One of the important characteristics of materials for orthopedic applications is the maximum elastic strain: for bone it is about 1.1%, for the high-porosity Ti-Nb-Z rs p e c i m e n si ti sa r o u n d3 % ,w h i c h guarantees that the implant will not be damaged before the bone [26][27][28]37]. …”
Section: Mechanical Behaviormentioning
confidence: 53%
“…The graphed pore size distributions (Fig. 9d,e,f) [26][27][28]. The lower pore size limit is related to the size of cells (~50 μm), while the upper pore size limit is related to the availability of binding sites and the anatomic dimensions of the pores of the specific bone tissue to be replaced.…”
Section: Ti-mentioning
confidence: 99%
“…Moreover, osteogenic differentiation potential of cells and the degree of matrix mineralization were also found to be better with larger pores (43). One possible explanation is that large pores would encourage faster nutrient and gas exchange, with less accumulation of metabolic waste in the central part of the scaffold (43). In addition, Kujala et al also reported that porous scaffolds with larger pores (505 ± 136 μm) had less fibrosis within the implant than scaffolds with smaller pores (259 ± 30 μm) (44).…”
Section: Discussionmentioning
confidence: 92%
“…Although it has been suggested that a wide range of pore sizes from 150-1000 μm allow bone ingrowth (41-43), Frosch et al found that large pores (600 μm) may allow much deeper and faster osteoblast ingrowth than small pores (300-500 μm). Moreover, osteogenic differentiation potential of cells and the degree of matrix mineralization were also found to be better with larger pores (43). One possible explanation is that large pores would encourage faster nutrient and gas exchange, with less accumulation of metabolic waste in the central part of the scaffold (43).…”
Section: Discussionmentioning
confidence: 97%
“…29 Previous studies found that bones prefer to grow in pores depth of 100-400 µm. 30 Mangano et al 31 investigated the biological response of direct metal laser sintering implant surfaces in vitro.…”
mentioning
confidence: 99%